Study of the effect of sodium 2-((4-amino-5-(thiophen-2-ylmethyl)- 4H-1,2,4-triazole-3-yl)thio)acetate toxic doses on rats heart tissue - A. A. Safonov; O. I. Panasenko; N. A. Al Khalaf (Aktualʹnì Pitannâ Farmacevtičnoï ì Medičnoï Nauki ta Praktiki, 2024)
Analysis of medicinal product safety is an important stage on the way to the entry of a synthetic compound into the pharmaceutical market. Along with the study of blood composition, scientists are actively analyzing the effect of toxic doses on the tissues of internal organs. Analyzing the toxic effect of compounds on heart tissue allows us to find out what damage substances can cause, which can have a direct impact on human health. Today, 1,2,4-triazole derivatives are very relevant and a huge number of publications is a confirmation of this.